Harmonising outcome measurement for child focused domestic abuse interventions. Reflections on the development and implementation of a core outcome set - Howarth, Emma; Feder, Gene; Barter, Christine; Powell, Claire (Frontiers in Psychiatry, 2024)
There is appetite in the UK to better measure the impact of domestic violence and abuse (DVA) interventions on children. The spread of outcomes-based commissioning means outcome measurement is no longer just the territory of academic researchers, but is now firmly within the purview of practitioners and policy makers. However, outcomes measured in trials only partially represent the views of those delivering and using services with respect to how success should be defined and captured. Even within trials there is huge inconsistency in the definition and measurement of important endpoints. This yields a body of evidence that is difficult to make sense of, ultimately defeatingdefeating the ends for which it was producedto improve the response to children and families who have experienced abuse. Development of Core Outcome Sets (COS) is seen as a solution to this problem, by establishing consensus across key stakeholder groups regarding a minimum standard for outcome measurement in trials, and increasingly in service delivery contexts. To date COS development has largely addressedaddressed outcomes relating to health conditions or interventions, with relatively limitedlimited application to public health challenges. We reflect on our efforts to develop a COS to evaluate psychosocial interventions for children and families experiencing DVA. We highlight the value of COS development as a mechanism for improving evidence quality, and ultimately thethe response to families experiencing abuse, andabuse., Finally, we make recommendations to researchers and COS guideline developers to support this broader application of COS methodology.